Jose Rizal - Jimenez, Butch; Duavit, Jimmy; Abaya, Marilou-Diaz; Abaya, Marilou-Diaz (GMA Network Films, 1999)
The film "Jose Rizal" explores the complex universe of the novelist's creative mind. In prison, as he awaits death, he sums his life--both real, as well as imagined; the people whom he loved as well as those he created in his novels; and judgement of his worth as a human being, and as an artist.